Creative Productive Learning Model to Enhance Understanding Narrative Competence in Primary Schools - D., Syamsiah; Salam, Rosdiah (Universitas Negeri Makassar, 2014)
The aim of the research is to describe the increase of student’ competence in understanding naration by using creative productive learning model. The kind of research is classroom action research. The subject of the research was thr teacher and 30 students’ of class V SDN Tidung Kota Makassar. The data was collected through observation and test. The result shows that there is an crease in learning process both in teacher and students activity and also an increase in students’ learning achievement test. The conclusion of this research is the implementation of creative productive learning model can increase studens’ competence in understanding naration